Pengembangan Buku Ajar Strategi Pembelajaran Berbasis Proyek dalam Bingkai Keterampilan Abad 21 untuk Calon Guru Sekolah Dasar - Fitri Indriani (Jurnal Syntax Admiration, 2024)
This research aims to produce project-based learning strategy textbook products within the framework of 21st century skills. This research is a type of ADDIE model development research with five stages, namely need assessment, Design, Development, Implementation, Evaluation.Data collection techniques using questionnaires. The results showed that the quality of the assessment of media experts, material experts and student responses obtained an overall score of 267.18 with an average number of 89.06. These results show that project-based learning strategy textbooks in the 21st century skills frame obtain "Very Good" criteria and can be used as companion books in learning strategy lectures. As a result, this research has produced project-based learning strategy textbook products in the frame of 21st century skills. Where this textbook product has been validated by media experts and material experts and has gone through a trial process limited to two classes totaling 61. In terms of quality, the assessment of media experts, material experts and student responses obtained an overall score of 267.18 with an average number of 89.06.